(untitled) (Journal of Environmental Science and Natural Resources, 2015)
Field experiments were carried out with Potato-Boro-T. aman cropping pattern at Birgonj, Dinajpur and Debigonj, Panchagarh during the consecutive years of 2011-12 to 2012-13 in the Old Himalayan Piedmont Plain Soils under agroecological zone (AEZ) 1 of North-West Bangladesh. The experiments were designed with eight treatments and laid out in randomized complete block design (RCBD) with three replications. The treatment combinations were: T1 (100%STB), T2 (T1 + 25% N), T3 (T1 + 25% NP), T4 (T1 + 25% NK), T5 (T1 + 25% PK), T6 (T1 + 25% NPK), T7 (75% of T1) and T8 (Control). Results indicated that application of different fertilizers significantly affected the grain yield at all of the locations. The highest yield was found in treatment T6 (T1 + 25% NPK). Statistically identical yield was observed in treatments T3, T4 and T5 at Birgonj, Dinajpur and T3 at Debigonj, Panchagar. All the treatment combinations gave significantly higher grain yield over the control at both of the locations. The highest straw yield was found in treatment T6 (T1 + 25% NPK). Statistically identical straw yield was found in T3 and T4 at Birgonj, Dinajpur and T1, T4 and T5 at Debigonj, Panchagarh. Significantly the lowest yield was obtained in control treatment (T8) in both of the locations. The highest total N uptake was observed in treatment T6 and a similar trend of total N uptake was observed for P uptake in both the locations. Treatment T6 showed the highest uptake of total K. The highest uptake of total S was observed in treatment T6 at Birgonj, Dinajpur and T3 at Debigonj, Panchagarh. However, the lowest total N, P, K and S uptake was observed in control treatment (T8) at both of the locations. The partial economic analysis showed the highest MBCR of 4.57 in T3 at Birgonj, Dinajpur and 4.75 in T6 treatments at Debigonj, Panchagarh respectively. Fertilizer doses recommended for Potato-Boro-T.aman pattern were N169P31K135S12Zn2B1 - N175P10K75S10Zn1B0.5 - N80P7.5K32S8 at Birgonj, Dinajpur and N188P23K169S8Zn2B1 - N188P10K94S8Zn1B0.5 - N84P7.5K40S6 at Debigonj, Panchagarh. DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22136 J. Environ. Sci. & Natural Resources, 7(1): 1-6 2014